PJMHS 2021
DOI: 10.53350/pjmhs211572175
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic, Loneliness and Digital Game Addiction

Abstract: Aim: The recent pandemic has spread all over the world and has become a common global problem. Pandemics leave significant marks on the memories. Going beyond a cause of disease or death, they can have consequences in many aspects; social, physical, and psychological. Aim of this study is to investigate the impact of the pandemic period on students’ loneliness and digital game addiction levels. Methods: The study group consisted of 398 volunteer 5th-8th grade students from Altın Vuruş Karate Center and Defne M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…Nine studies reported the prevalence of GD during the early stages of the COVID-19 pandemic as follows: 11 percent among Vietnamese adolescents, 81 19 percent among Italian children and adolescents, 82 5.3 percent among Chinese children and adolescents, 83 16.6 percent among Spanish university students, 84 2.5 percent among medical students in Malaysia, 85 4.1 percent among Japanese middle-aged adults (8.5 percent among younger than 30), 77 15 percent among Chinese adolescents, 86 8.5 percent in college students from Nepal, 87 and 4.5 percent among Malaysian university students. 88 The 11 studies conducted on children and adolescent GD were associated with: age (i.e., being adolescent), 79,82,89 gender (i.e., being male), [82][83][84]86,[89][90][91][92] maladaptive coping regulatory styles, 86 poor social support, 83,86,89 depressive and anxiety symptoms before the COVID-19 pandemic, 76,92 poor mental health, 83 academic stress, 86 unhealthy parental care styles, [81][82][83] addictive gamer profile, 90,91 and excessive use of social networks. 84 With regard to adults, eight studies showed an increased risk of developing GD symptoms in association with age (i.e., being younger than 30 years), 77,79 gender (i.e., being male), 79,87 loneliness, 79,93 maladaptive self-regulation style,…”
Section: Study Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine studies reported the prevalence of GD during the early stages of the COVID-19 pandemic as follows: 11 percent among Vietnamese adolescents, 81 19 percent among Italian children and adolescents, 82 5.3 percent among Chinese children and adolescents, 83 16.6 percent among Spanish university students, 84 2.5 percent among medical students in Malaysia, 85 4.1 percent among Japanese middle-aged adults (8.5 percent among younger than 30), 77 15 percent among Chinese adolescents, 86 8.5 percent in college students from Nepal, 87 and 4.5 percent among Malaysian university students. 88 The 11 studies conducted on children and adolescent GD were associated with: age (i.e., being adolescent), 79,82,89 gender (i.e., being male), [82][83][84]86,[89][90][91][92] maladaptive coping regulatory styles, 86 poor social support, 83,86,89 depressive and anxiety symptoms before the COVID-19 pandemic, 76,92 poor mental health, 83 academic stress, 86 unhealthy parental care styles, [81][82][83] addictive gamer profile, 90,91 and excessive use of social networks. 84 With regard to adults, eight studies showed an increased risk of developing GD symptoms in association with age (i.e., being younger than 30 years), 77,79 gender (i.e., being male), 79,87 loneliness, 79,93 maladaptive self-regulation style,…”
Section: Study Outcomesmentioning
confidence: 99%
“…In line with what was observed in previous studies, [122][123][124] in the present systematic review, gender and age differences with regard to GD emerged: potentially problematic gaming symptoms were found to be more likely among males than females 79,87 and among younger gamers. 77,79,82,89 Furthermore, high levels of loneliness and poor social support, 79,83,86,89,93 maladaptive coping regulatory styles, 86,88 and depressive and anxiety symptoms 76,79,83,88,92,94 resulted in risk factors for GD in both young people and adults. Such results support what was reported by previous studies, in which these factors were indicated as risk elements for problematic gaming.…”
Section: Principal Findingsmentioning
confidence: 99%
“…During the COVID-19 pandemic, there was an increase in school-aged children's gaming disorder, which is a behavioral addiction (Çakıroğlu et al, 2021;Choi et al, 2021) reported an increase in smartphone addiction tendencies among children. Similarly, Ekinci et al (2021) found that the level of game addiction among children also increased. According to another study conducted during the pandemic, the rise in preschool children's addiction to digital games has had an adverse effect on their social and emotional development (Şenol et al, 2023).…”
Section: The Importance Of the Study And Research Questionsmentioning
confidence: 89%
“…Bilişsel esneklik düzeyi, bireyin yüzleşmekte olduğu durum ya da olayları kontrolünün dışında olarak değerlendirmesiyle azalabilmektedir. Bu anlamda kaygı ve strese neden olabilecek koşulların algılanması ve değerlendirilmesindeki çeşitlilik, bilişsel esneklik düzeylerindeki farklılıklara temel oluşturabilmektedir (Aktepe, 2022;Gabrys, Howell, Cebulski, Anismana ve Matheson, 2019) (Currie, 2021;Gainer ve diğerleri, 2021;Geng ve diğerleri, 2021;Tambelli, Forte, Favieri ve Casagrande, 2021;Wild, McKinnon, Wilkins ve Browne, 2022), alkol/madde/tütün bağımlılıkları, davranışsal bağımlılıklar (Dubey ve diğerleri, 2020;Ekinci, Karaali, Parçali, Suner ve Satilmiş, 2021;Elsayed, 2021;Fidancı, Aksoy, Yengil Taci, Ayhan Başer ve Cankurtaran, 2021;Naaj ve Nachouki, 2021;Pirnia ve diğerleri, 2020) yeme ve uyku bozuklukları (Giel, Schurr, Zipfel, Junne ve Schag, 2021;Inönü Köseoğlu, 2021;Marvaldi, Mallet, Dubertret, Moro ve Guessoum, 2021;Phillipou ve diğerleri, 2020) dahil olmak üzere birey ve toplum ruh sağlığına birçok olumsuz etkisi olduğuna yönelik bulgular sunmaktadır.…”
Section: Sonuç Tartışma Ve öNerilerunclassified